Effect of home-based interventions on basic activities of daily living for patients who had a stroke: a systematic review with meta-analysis - Ping Qin; Canxin Cai; Xuan Chen; Xijun Wei (BMJ Open)
Objectives To investigate the effectiveness of home-based interventions in improving the ability to do basic activities of daily living in patients who had a stroke.Methods Randomised controlled trials were searched through MEDLINE, Embase and CINAHL from their inception to 31 December 2021. We included studies involving home-based intervention prescribed by professionals and implemented at patients’ homes. The characteristics of these studies were collected. Risk of bias of individual study was assessed by Physiotherapy Evidence Database scale. Meta-analyses were performed where studies reported comparable interventions and outcomes.Results In total, 49 studies were included in the systematic review and 16 studies had sufficient data for meta-analyses. The short-term effect of home-based intervention showed no significant difference when compared with institution-based intervention (standardised mean difference (SMD)=0.24, 95% CI −0.15 to 0.62, I2=0%). No significant difference was found between home-based intervention and usual care for long-term effect (SMD=0.02; 95% CI −0.17 to 0.22; I2=0%). Home-based rehabilitation combined with usual care showed a significant short-term effect on the ability to do basic daily activities, compared with usual care alone (SMD=0.55; 95% CI 0.22 to 0.87; p=0.001; I2=3%).Conclusion Home-based rehabilitation with usual care, which varied from no therapy to inpatient or outpatient therapy, may have a short-term effect on the ability to do basic activities of daily living for patients who had a stroke compared with usual care alone. However, the evidence quality is low because of the limited number of studies and participants included in the meta-analysis and the possible publication bias. Future research is needed to investigate the effectiveness of home-based rehabilitation in groups with stratification by stroke severity and time since stroke onset, with elaboration of details of the home-based and the control interventions. Moreover, more high-quality studies are required to prove the cost-effectiveness of newly developed strategies like caregiver-mediated rehabilitation and telerehabilitation.The primary source of funding The Medical Research Fund of Guangdong Province (No: A2021041).